Recherches interdisciplinaires sur l’alimentation et l’évacuation des eaux du palais de Dioclétien à Split - Marasović, Katja; Margeta, Jure (Antiquité Tardive - Late Antiquity - Spätantike - Tarda Antichità, 2021)
Abstract From 2014 until 2018, at the Faculty of Civil Engineering, Architecture and Geodesy of the University of Split, the project “Roman Water Systems of Salona and the Diocletian’s Palace and their Impact on the Sustainability of the Urban Environment” was carried out by an interdisciplinary team of archaeologists, architects and civil engineers. All archival sources, published papers and unpublished reports of archaeological excavations were gathered and analysed, and led to new conclusions on the Roman urban water systems of Salona and the Palace. This paper presents some of these very recent results regarding the water supply and sewage system of Diocletians Palace in Split. Notably, the aqueduct leading to the Diocletian’s Palace has been well preserved (since at the end of the 19th century it was reconstructed, with more than half of its route still used for the water supply of the city of Split). Within the Palace itself, a great part of the sewage system was equally well preserved and allows that its original structure and features may be reconstructed. Both, the aqueduct as well as the sewage system give an excellent insight in the planning and execution of Roman urban water systems. Surprisingly, its planned approach, parameters, conception as well as specific solutions and details are much in accordance with the nowadays standard practice of water engineering, that has not changed siginificantly.